Analisis Strategi Pemasaran Untuk Meningkatkan Penjualan Produk Box Panel - Galih Alfikry (RESWARA, 2023)
Queues are part of everyday life. Queues occur when the number of customers to be served exceeds the available service capacity. This queuing situation can be found on several occasions, one of which is at the delivery counter at PT Batik Ekspedisi Indonesia. The aim of this research is to analyze the customer service queuing system that occurs at PT BEI at the delivery counter. Which describes how the queue conditions are and to find out whether the service provided to customers has been carried out optimally, even though the company already has several goods delivery counters. For this reason, modeling and simulation using the Monte Carlo method with a Multi Channel Single Phase queuing system are used. And using Arena software to create a simulation model of the queue model at PT BEI. This research uses the observation method or goes directly into the field and carries out library research and laboratory research. The results displayed are in the form of a simulation using Arena software on the desktop layer.